The reality and dimensions of the federal general budget of the Republic of Iraq (2005-2021) - Mohammed, Khorsheed; Yassin Al-Saffar, Ahmed (Humanities Journal of University of Zakho, 2023)
Abstract: This study focused on the traditional method adopted by Iraq in preparing the general budget in light of the developments in the volume of resources and spending so that it is not consistent with the accompanying weakness in the volume of amounts spent on investment projects, which can negatively affect future generations and not enable them to continue development , which requires investing the state’s public revenues in investment projects such as infrastructure projects, according to a system that serves most members of society in order to contribute to solving the problems of unemployment and poverty, which ensures a permanent increase in the average per capita income. The research reached a set of conclusions, the most important of which is the clarity of the imbalance in the structure of the current budget and the failure to reduce class differences to solve the problem of poverty and unemployment, and the study concluded that there is a clear imbalance in the structure of investment expenditures in favor of the industrial sector. To the extractive oil industry sector designated for export, and from the results of the study, it was also found that the traditional budget of Iraq is unable to provide economic efficiency, especially with regard to planning and performance, because it is not focused on goals. In the end, the study presented a number of proposals, including an attempt to correct the structure of the general budget and the need to change the pattern of the general budget in Iraq, and the distribution of public expenditures on a functional and not institutional basis, and to address the deficit in the Iraqi public budget by rationalizing public spending with the need not to exceed the growth of expenditures the current growth occurring in revenues, and finally giving the economic development sector more attention in terms of its total percentage in the Iraqi general budget.